Characterization of intentional lurasidone ingestions using the United States National Poison Data System. (1st December 2020) - Weiss, S. J.; Cueto-Vilorio, V. A.; Dharmaraj, R.; Barolia, D.; Nashat, A.; Walsh, S. J.; Simpson, S. E.
Abstract: Introduction: The ziprasidone analogue lurasidone is approved for the treatment of schizophrenia and bipolar disorder for adults and children older than 10 years. Small studies and case reports suggest lurasidone overdose is not generally associated with major adverse effects, but no large sample has been published. Objective: To describe intentional lurasidone overdoses reported to poison centers. Methods: Retrospective analysis of single-substance intentional lurasidone ingestions from the National Poison Data System (NPDS) from 2011 to 2018. Results: There were 1753 single-substance intentional overdoses. Average age was 28.6 years (SD = 13.3 years) and 1199 (68.4%) of patients were female. Most cases (86.6%) were coded as suspected suicide. Regarding final management site, 1143 (65.2%) were discharged or admitted to psychiatric facilities; 328 (18.8%) were admitted, half of whom were admitted to critical care units (CCUs). Major effect was coded in 12 (0.7%), moderate effect in 259 (14.8%), minor effect in 531 (30%), and no effect in 614 (35%). There were no deaths. For cases for which dose information was available, there was not a statistically significant difference between median doses when analyzed by clinical effect. Most common adverse effects were drowsiness (449, 25.6%), tachycardia (254, 14.5%), vomiting (121, 6.9%), and hypertension (115, 6.6%). Most cases had either no therapy reported, or therapy was recommended by the poison center but confirmed not to have been administered (1010, 57.6%). Of the 164 patients admitted to CCUs, 80 (48.8%) received either no therapy or intravenous fluids alone. Discussion: These data suggest major effects are uncommon from lurasidone overdose. Despite a high rate of admission to CCUs, a substantial proportion received no critical therapies. Conclusions: This report demonstrates intentional lurasidone overdoses reported to poison centers generally have a favorable clinical course.